Seismic Analysis of a Tall Structure Considering Flat and Grid Slab Diaphragm Using Analysis Tool Staad. Pro - Singh, Paritosh; Joshi, Rajesh (International Journal of Scientific Research in Civil Engineering, 2019)
Modern slab systems have shown great potentials in the field of conventional slab casting. Recent advances in the field of RCC Design are related to the use of Flat Slabs and Grid Floors. Flat slabs are versatile elements which are widely adopted in construction providing quick construction, minimum depth, and allowing flexible column grids. In flat slabs, the beams used in conventional slabs are taken away and the slab is made to rest directly over the columns. In case of higher loads, a drop panel or a column head may be provided to reduce the intensity of loads. They are particularly appropriate for areas where tops of partitions need to be sealed to the slab soffit for acoustic or fire reasons. On the other hand, grid floor systems consist of a large number of beams spaced at regular intervals in perpendicular directions, monolithic with slab. The rectangular or square void thus formed in the ceiling is advantageously utilized for works such as providing concealed architectural lighting. Grid floors are generally employed for architectural reasons in case of large rooms such as theatre halls, auditoriums, vestibules, and show rooms of shops where column free space is the main requirement. This study focuses on studying the behavior of conventional slab, flat slab and grid slab separately. A comparative study was done to identify the best slab system. The modeling was done in Staad.pro in which square, hexagonal and octagonal geometries were considered for the structures. The models were also developed for different number of floors taking 10, 20 and 30 storey structure designs. Seismic loadings were considered separately to evaluate the performance of all the 27 models and conclusions were drawn on the best framing system. In this structure cost analysis of all these structures are also considered.